Análisis de procesos licitatorios para contratos de obra pública y asignación de riesgos para un caso específico colombiano (2020)
The objective of public works contracts in Colombia is to delegate the execution of civil works in the national territory, for this bidding processes or contests are held in order to choose the best bidder for the development of each specific work, taking into account factors of great importance such as experience or trajectory, financial muscle and technical capacities, factors that will allow the work to be executed by a proponent who complies with the provisions of the specifications, thus reducing the risks associated with said execution. The general objective of this research proposal is to analyze and study the bidding process for public works contracts and the risks associated with this type of bidding based on what is established in the book MANUAL DE PROCEDIMIENTO DE LA CONTRATACIóN ESTATAL by Javier Gámez (2001) and in the articles LA ASIGNACION O DISTRIBUCION DE RIESGOS EN LA CONTRATACION DE OBRAS PUBLICAS Y LA RESPONSABILIDAD CONTRACTUAL POR LOS RIESGOS PREVISIBLES, ENTRE LA AUTONOMIA DE LA VOLUNTAD PRIVADA Y LA RIGUROSIDAD DE LAS NORMAS DE LA CONTRATACION PUBLICA de Fonseca, E (2002) and Sarmiento, J (2016) respectively. Taking the foregoing into account, the main information was gathered within a project that is part of a public road tender presented at SECOP in 2009 in the department of Huila and executed by the PALETARA 2009 consortium and a comparison was made regarding to the risk allocation process with what is specified in the MANUAL PARA LA IDENTICACIóN Y COBERTURA DEL RIESGO EN LOS PROCESOS DE COTRATACIóN (2013).